The Influence of Gadget Use Intensity on Students' Narrative Writing Skills at SDN 34 Kendari - Saputra, Erwin Eka; Kasmawati, Kasmawati (International Journal of Management and Education in Human Development, 2025)
Advances in digital technology have both positive impacts and challenges in education, particularly for elementary school students. Gadgets, as versatile devices, have become a part of children's lives, providing entertainment, communication, and access to information. However, high levels of gadget use are often associated with a decline in basic literacy skills , including narrative writing skills. This study aims to analyze the effect of gadget use intensity on elementary school students' narrative writing skills. The research method used a quantitative approach with an experiential design. post facto. The study was conducted at SDN 34 Kendari in the even semester of the 2024/2025 academic year with a population of 60 fifth-grade students and a sample of 30 students selected through purposive sampling. The research instruments were a questionnaire to measure the intensity of gadget use and a narrative writing test that assessed aspects of theme, plot, characters, setting, and writing mechanics. Data were analyzed using simple regression. The results showed a significant effect of gadget use intensity on narrative writing ability (p < 0.05). The coefficient of determination (R²) of 0.41 indicated that 41% of the variation in narrative writing ability was influenced by gadget use intensity, while 59% was influenced by other factors such as reading interest, learning environment, and motivation. The results of this study indicate that the higher the intensity of unsupervised gadget use, the lower the students' narrative writing ability. Therefore, an active role of teachers and parents is needed in directing the use of gadgets to support literacy activities . This study is expected to be a consideration in developing digital literacy- based learning strategies in elementary schools.